Bacterial endotoxin (lipopolysaccharide) binds to the surface of gold nanoparticles, interferes with biocorona formation and induces human monocyte inflammatory activation. Issue 9 (26th November 2017) - Li, Yang; Shi, Zhenzhen; Radauer-Preiml, Isabella; Andosch, Ancuela; Casals, Eudald; Luetz-Meindl, Ursula; Cobaleda, Macarena; Lin, Zhoumeng; Jaberi-Douraki, Majid; Italiani, Paola; Horejs-Hoeck, Jutta; Himly, Martin; et al.
Abstract: Nanoparticles (NPs) are easily contaminated by bacterial endotoxin (lipopolysaccharide [LPS]). The presence of LPS can be responsible for many immune/inflammatory effects attributed to NPs. In this study, we examined the effects of LPS adsorption on the NP surface on the formation of a biocorona in biological fluids and on the subsequent inflammation-inducing activity of NPs. Different gold (Au) NPs with sizes ranging from 10 to 80 nm and with different surface functionalization (sodium citrate, lipoic acid, and branched polyethyleneimine (BPEI), or polyethylene glycol (PEG)) were exposed to E. coli LPS under different conditions. The binding capacity of LPS to the surface of AuNPs was dose- and time-dependent. LPS attached to sodium citrate and lipoic acid coatings, but did not adhere to BPEI- or PEG-coated NPs. By computational simulation, the binding of LPS to AuNPs seems to follow the Langmuir absorption isotherm. The presence of LPS on AuNP surface interfered and caused a decrease in the formation of the expected biomolecular corona upon incubation in human plasma. LPS-coated AuNPs, but not the LPS-free NPs, induced significant inflammatory responses in vitro . Notably, while free LPS did also induce an anti-inflammatory response, LPS bound to NPs appeared unable to do so. In conclusion, the unintentional adsorption of LPS onto the NP surface can affect the biocorona formation and the inflammatory properties of NPs. Thus, for an accurate interpretation of NP interactions with cells, it is extremely important to be able to distinguish the intrinsic NP biological effects from those caused by biologically active contaminants such as endotoxin.